Supervision and monitoring to assess quality of outreach immunization sessions in a rural area using a checklist - Bhaskar, Ambika R.; Solanki, Mridula (International Journal Of Community Medicine And Public Health, 2020)
Background: Immunization is one of the most cost-effective interventions to prevent the suffering that comes from avoidable sickness, disability and death. Outreach immunization services ensure that immunization is available to children who are unable to access a general practice in a timely fashion for their immunization events. Effective supervision and monitoring will help in improving quality and coverage of immunization. Methods: This was an observational cross-sectional study conducted in the rural field practice area of a tertiary care hospital. 50 outreach sessions held in various outdoor places including Anganwadi were supervised and monitored using checklist. 110 mothers and 20 stakeholders were interviewed. Immunization records were assessed. Results: Outreach immunization sessions were found to be of good quality. 89% children were fully immunized. ANMs and ASHAs were of the opinion that outreach session has significantly raised immunization coverage. 75.4% mothers had knowledge about services provided by outreach sessions. Conclusions: There was increase in immunization coverage due to outreach sessions. There is need for adequate supervision on safety injection practices and regular timely incentive to ASHA.